INFLUENCE OF INTESTINAL MICROBIOTA ON THE COURSE AND OUTCOME OF OBSTRUCTIVE BRONCHITIS IN FREQUENTLY SICK CHILDREN - Ibragimova Марина (International Journal of Scientific Pediatrics, 2025)
Introduction. Despite the progress in antibacterial therapy and intensive care, obstructive bronchitis continues to occupy a leading position among childhood diseases worldwide. Recently, more and more attention has been paid to the role of intestinal microflora in immune regulation and its impact on the course of infections, including bronchitis. This work focuses on the analysis of modern data on the effect of intestinal microflora on the course and outcome of obstructive bronchitis in children. Objective: to study the effect of intestinal microflora on the course and outcome of obstructive bronchitis in frequently ill children. Materials and methods of the study. To study this problem, we conducted research in the pediatric departments of the Samarkand branch of the Republican Scientific Center for Emergency Medical Care, in the gastroenterology and pulmonology department of the Samarkand Regional Children’s Multidisciplinary Medical Center. The study included 52 patients with obstructive bronchitis aged 1 to 10 years. Of these: Group I - 26 patients with obstructive bronchitis who received combination therapy with probiotics. Group II - 26 patients with obstructive bronchitis who received traditional treatment. The control group consisted of 20 practically healthy children. Conclusions. The state of the intestinal microbiota has a significant impact on the course and outcome of obstructive bronchitis in children. Dysbacteriosis can contribute to the development of inflammatory processes and a decrease in the effectiveness of the immune response. Healthy microflora helps maintain a balance between pro- and anti-inflammatory reactions, which reduces the risk of severe obstructive bronchitis and complications. Correction of microbiota with probiotics and prebiotics can improve the immune response, reduce the severity of the disease and speed up recovery. Convenient to use, higher efficiency, the absence of side and adverse effects allow us to recommend this treatment for widespread use in pediatric practice.